Developing Online Professional Networks for Undergraduate Occupational Therapy Students: An Evaluation of an Extracurricular Facilitated Blended Learning Package. (June 2014) - Bodell, Sarah; Hook, Angela
This practice analysis evaluates an extra curricular opportunity provided to undergraduate occupational therapy students. A blended learning package was designed and facilitated by two experienced educators, aiming to equip students with the knowledge and skills required to use online social media to create professional networks and facilitate continuing professional development. Feedback was sought on the design and impact of the package, with students revealing an increased confidence in online professional networking. Suggestions for change included more guidance about online professionalism. It can be concluded that the package is effective in preparing students to use the online environment for continuing professional development.